Integration of Islamic Values in the Traditional Wedding Customs of the Malay Community in Pekanbaru - Juswandi, Juswandi; Hermansyah, Hermansyah; Nijal, Lasri; Bin Mohd Said, Bambang Suhartono (Sosial Budaya, 2023)
This research aims to analyze the Islamic elements present in the traditional wedding customs of the Malay community in Riau. The study adopts a phenomenological case study method to investigate this cultural phenomenon. The findings reveal a strong integration of Malay customs and Islamic values within the Riau Malay culture. The preference for the term "nikah-kawin" among the Riau Malay community reflects the significance of both cultural traditions and religious values in their marriage institution. Furthermore, Islamic values such as respect for parents, prayer, and gratitude are also integrated into various Riau Malay customary ceremonies. Within this context, the research demonstrates how the Riau Malay culture exemplifies the harmonious fusion of religion and tradition, contributing to the formation of a strong identity and enriching positive values within the local community. To preserve and enhance the cultural heritage rooted in Islamic values, it is crucial to enhance the understanding and awareness of the importance of preserving the Riau Malay cultural heritage. Further comprehensive and inclusive research is warranted to deepen the understanding of this phenomenon.